From "villages of longevity" to "villages of cancer"? The emotional geography of tourism development in Bama, China. (August 2021) - Huang, Xiang; Lin, Shuyuan; Cui, Qingming
Abstract: Studies on residents' attitudes toward tourism development either assume that residents are unemotional "homo economics" or frame their emotions as forming rigid patterns. Following emotional approach, this study on Bama in China argues that residents' emotions toward tourism development and its environmental impacts are dynamic and ambivalent. Qualitative methods such as semi-structured interview and observation were used to collect data. The results show that during tourism development, interactions with outsiders encouraged the residents to realize the symbolic healing effects of their living environment and develop feelings of amazement and pride. However, continuous development had negative effects on the physical and symbolic environments, which induced complex emotional responses in the residents, including dislike, dissatisfaction, tolerance, anger, and fear. However, in this wealth-building stage, the residents' ecological grief is compensated by economic growth and has not evolved to resisting actions against development. The emotional ambivalence between eagerness to economic prosperity and concern of ecological loss still exists in Bama and was enhanced in the shutdown of tourism caused by the COVID-19 pandemic. Further research should explore whether, and how ecological concerns about a tourism location may override potential economic gains and encompass anti-development actions. Highlights: Development can stimulate residents to value their living environment and develop feelings of amazement and pride. Tourism development has negative effects on the physical and symbolic environments of wellness tourism destinations. Negative environmental changes induce complex emotions, such as dislike, dissatisfaction, tolerance, anger and fear, in residents. In the wealth-building stage, residents' ecological grief does not necessarily evolve to resisting actions and can be compensated by economic growth. The COVID-19 pandemic has strengthened the emotional ambivalence between eagerness to achieve economic prosperity and concerns about environmental loss.